2021
DOI: 10.3390/s21020401
|View full text |Cite
|
Sign up to set email alerts
|

Tablet Technology for Writing and Drawing during Functional Magnetic Resonance Imaging: A Review

Abstract: Functional magnetic resonance imaging (fMRI) is a powerful modality to study brain activity. To approximate naturalistic writing and drawing behaviours inside the scanner, many fMRI-compatible tablet technologies have been developed. The digitizing feature of the tablets also allows examination of behavioural kinematics with greater detail than using paper. With enhanced ecological validity, tablet devices have advanced the fields of neuropsychological tests, neurosurgery, and neurolinguistics. Specifically, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 92 publications
1
3
0
Order By: Relevance
“…Investigators of everyday habits have chosen behaviours that have critical automatic stimulus-response components 30 and versions that can be performed in the laboratory while BOLD signals are measured by fMRI imaging. Examples of such tasks include reading, where comparisons are made between real words of different familiarity and emotional content, foreign words and pseudo-words 31 ; writing and drawing 32, 33 walking on a special apparatus 34 ; and driving an MR-compatible driving simulator (Box 1A; Choi et al, 2017; Cummine et al, 2016; Huth et al, 2016; Karimpoor et al, 2015; Martínez et al, 2016, 2018; Oberhuber et al, 2013; Varotto et al, 2020; Yang et al, 2018). The specific question we were interested in is whether recently established laboratory habits and those developed in everyday life engaged the same, partially overlapping or separate neural circuits in the brain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators of everyday habits have chosen behaviours that have critical automatic stimulus-response components 30 and versions that can be performed in the laboratory while BOLD signals are measured by fMRI imaging. Examples of such tasks include reading, where comparisons are made between real words of different familiarity and emotional content, foreign words and pseudo-words 31 ; writing and drawing 32, 33 walking on a special apparatus 34 ; and driving an MR-compatible driving simulator (Box 1A; Choi et al, 2017; Cummine et al, 2016; Huth et al, 2016; Karimpoor et al, 2015; Martínez et al, 2016, 2018; Oberhuber et al, 2013; Varotto et al, 2020; Yang et al, 2018). The specific question we were interested in is whether recently established laboratory habits and those developed in everyday life engaged the same, partially overlapping or separate neural circuits in the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, investigators have chosen behaviours that have significant automatic stimulus-response components (Ceceli et al, 2020) and can be performed in the laboratory while both behaviour and fMRI BOLD signals are measured simultaneously. Examples of such tasks include reading, where comparisons are made between real words of different familiarity and emotional content, foreign words and pseudo-words (Cummine et al, 2016); writing and drawing (Lin et al, 2021; Yang et al, 2018) walking on a special apparatus (Martínez et al, 2018); and driving an MR-compatible driving simulator (Box 1A; Choi et al, 2017; Cummine et al, 2016; Huth et al, 2016; Karimpoor et al, 2015; Martínez et al, 2016, 2018; Oberhuber et al, 2013; Varotto et al, 2020; Yang et al, 2018). The specific question we addressed in the current study is whether the BOLD activity patterns reported for stimulus-response associations acquired in everyday life are the same, partially overlapping or separate from those described for recently established laboratory habits (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…This study confirmed that specialized tablet writing was suitable for mediating language-motor transformations (e.g., phoneme-grapheme conversion; Planton et al, 2017). Lin et al (2021) studied brain activation when adults wrote and drew on regular tablets; the study found that tablets were an excellent device for approximating traditional paper and pencil writing and drawing tasks (Lin et al, 2021). This study yielded information on the effect of various written outputs on behavioral kinematics, recording capabilities, and neurolinguistics.…”
Section: Unique Technology Features For Spelling and Phonology Educatorssupporting
confidence: 57%
“…This study yielded information on the effect of various written outputs on behavioral kinematics, recording capabilities, and neurolinguistics. The study improved understanding of the mental processes that support writing performance (Lin et al, 2021). These neurolinguistic research studies confirmed that using a digital tablet with a stylus or finger-writing was equivalent to paper and pencil writing, and it improved word memory and helped connect sounds to symbols.…”
Section: Unique Technology Features For Spelling and Phonology Educatorsmentioning
confidence: 52%